Unraveling the effects of leadership and motivation factors on employee engagement evidence from the U.S. Federal agencies - Ugaddan, Reginald G. (Philippine Journal of Public Administration, 2014)
This article discusses employee engagement, a growing distinct construct in the field of human resource management and development in enhancing public sector performance and well-being of employees. While many studies have explored a set of determinants of employee engagement, few studies ascertain the relationship and the role of political and career senior executive leadership of the Senior Executive Service (SES) and motivation factors (i.e., intrinsic motivation and empowerment). This article shows that two types of leadership in the SES are highly associated with the employee engagement; and that intrinsic motivation and empowerment are effective mediators of SES and employee engagement. Using the Merit Principles Survey 2010 as well as importing insights derived from a set of organizational theories, this study develops an antecedent-mediator-outcome model and empirically examines the direct and indirect effects of SES and motivation factors on employee engagement. The results showed that political senior executive leadership is positively related to empowerment but negatively related to intrinsic motivation. On the other hand, career senior executive leadership is highly related to intrinsic motivation and empowerment. The relationship of the SES and employee engagement is partially mediated by the employee's intrinsic motivation and empowerment.